2019
DOI: 10.1002/zaac.201900017
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structures, and Properties of Two Novel CL‐20‐based Cocrystals

Abstract: In recent years, cocrystallization has emerged as an effective way of tuning the properties of compounds and has been widely used in the field of energetic materials. In this study, we have prepared two novel cocrystals of CL-20 and methylimidazole, including a 1:2 CL-20 / 2-mercapto-1-methylimidazole (1) and a 1:4 CL-20 / 4-methyl-5-nitroimidazole (2). Cocrystal 1 has good physical and detonation properties (ρ 1 = 1.652 g·cm -3 , D 1 = 7073 m·s -1 , P 1 = 21.6 GPa); however, cocrystal 2 shows higher propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…In addition, an interesting phenomenon is that multiple conformers of CL-20 or HMX are found in EMCCs. The CL-20-based EMCCs possess the largest population among the observed EMCCs except for a large quantity of energetic solvates of HMX. ,,, This can be attributed to the remarkable detonation performance, while the rather high sensitivity requires an improvement of CL-20 itself. With regard to the molecular structure of CL-20, its cage frame is rigid, while its nitro groups can be swung readily, giving it a certain flexibility to implement the conformational transformation. , With respect to the CL-20 molecules in CL-20-based EMCCs, five types of conformers are found, including β, γ, η, ε, and ζ forms (Figure ).…”
Section: Intermolecular Interactions In Emccsmentioning
confidence: 99%
“…In addition, an interesting phenomenon is that multiple conformers of CL-20 or HMX are found in EMCCs. The CL-20-based EMCCs possess the largest population among the observed EMCCs except for a large quantity of energetic solvates of HMX. ,,, This can be attributed to the remarkable detonation performance, while the rather high sensitivity requires an improvement of CL-20 itself. With regard to the molecular structure of CL-20, its cage frame is rigid, while its nitro groups can be swung readily, giving it a certain flexibility to implement the conformational transformation. , With respect to the CL-20 molecules in CL-20-based EMCCs, five types of conformers are found, including β, γ, η, ε, and ζ forms (Figure ).…”
Section: Intermolecular Interactions In Emccsmentioning
confidence: 99%
“…In other words, it is a promising strategy for in-depth tuning of properties of EMs. In addition, it is found that the CL-20/MMI cocrystals with good detonation properties are extremely insensitive to impact and friction . Some CL-20-based cocrystals with high energy and low sensitivity can meet any requirements for high-energy components in the propellant formulations.…”
Section: Sensitivity Thermal Decomposition and Detonation Propertiesmentioning
confidence: 99%
“…Based on the types of EMs that were used to make cocrystals with nitramine explosives, it is found that and the major coformers include three types, which are nitramine, nitrobenzene, and nitrated azoles . Moreover, except for the CL-20-based cocrystals with energetic coformers, mostly CL-20/nonenergetic cocrystals (e.g., CL-20/MMI cocrystal, CL-20/2,4-MDNI cocrystal) have been prepared. The energetic cocrystals form a new structure, which may effectively improve the physicochemical properties, safety, and detonation performance, where in particular the sensitivity could be significantly reduced. …”
Section: Introductionmentioning
confidence: 99%
“…Researchers have already prepared many CL‐20‐based cocrystals in solution . The above molecular conformers of CL‐20 have all been observed in CL‐20‐based cocrystals in ambient conditions; the γ ‐form and the β ‐form were the most common conformers of the reported CL‐20 cocrystals. As CL‐20 is a polymorphic molecule, the mechanism of its conformational transformation in solvents is quite complicated, and the influence of solvents still requires further study.…”
Section: Introductionmentioning
confidence: 98%